A new genus and species of bark mantis from Thailand, with an updated key to the bark mantis genera of the Oriental region (Insecta: Mantodea) - Schwarz, Christian J.; Ehrmann, Reinhard (Zootaxa, 2017)
A new genus and species of praying mantis, Paratheopompa siamensis n. gen. n. sp. from Thailand is described and figured. The species is most closely related to the Oriental genera Humbertiella Saussure, 1869 and Theopompa Stål, 1877, filling the morphological gap between the two genera. A key to the Oriental bark mantises of the Humbertiella group is provided.